ANALYTICAL STUDY OF THE ROLE MODEL OF THE RASULULLAH'S LEADERSHIP CHARACTERISTICS AND ITS IMPLEMENTATION IN ISLAMIC EDUCATIONAL INSTITUTIONS - Yusri M. Daud (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
The urgency of role modeling the leadership characteristics of Rasulullah and its implementation in Islamic educational institutions is very important because Rasulullah Muhammad SAW is the main example in all aspects of life, including leadership. Implementing the leadership characteristics of the Prophet Muhammad in Islamic educational institutions not only forms strong and effective leadership, but also creates a harmonious and productive learning environment. By taking the Prophet as an example, leaders and managers of Islamic educational institutions can ensure that they not only achieve educational goals academically, but also build strong character and morals in their students in accordance with Islamic teachings. This research is a literature study. This paper uses three types of source materials, namely: primary, secondary and tertiary. The analytical technique applies three analytical techniques: deductive, inductive and comparative. The results of the research show that the characteristics of the Prophet's leadership include: Godly, Universal, Humanist, Realistic, Harmonious, Just, Easy and Dynamic. The role of the Prophet Muhammad SAW began with forming a new people who had their own intellectual abilities, behavior, morals, laws, legislation and language. So that if the individuals in it grow and interact with other worlds, whose beliefs and behavior are completely different, with other ummah, the leadership models include, among others, education that begins in the family, education by reading and writing the Koran and establishing educational institutions